A Preliminary Study of the Effects of Attentive Music Listening on Cochlear Implant Users’ Speech Perception, Quality of Life, and Behavioral and Objective Measures of Frequency Change Detection - Firestone, Gabrielle M.; McGuire, Kelli; Liang, Chun; Zhang, Nanhua; Blankenship, Chelsea M.; Xiang, Jing; Zhang, Fawen (Frontiers in Human Neuroscience, 2020)
Introduction. Most cochlear implant (CI) users have difficulty in listening tasks that rely strongly on perception of frequency changes (e.g., speech perception in noise, musical melody perception, etc.). Some previous studies using behavioral or subjective assessments have shown that short-term music training can benefit CI users’ perception of music and speech. Electroencephalographic (EEG) recordings may reveal the neural basis for music training benefits in CI users. Objective. To examine the effects of short-term music training on CI hearing outcomes using a comprehensive test battery of subjective evaluation, behavioral tests, and EEG measures. Design. Twelve adult CI users were recruited for a home-based music training program that focused on attentive listening to music genres and materials that have an emphasis on melody. The participants used a music streaming program (i.e., Pandora) downloaded onto personal electronic devices for training. The participants attentively listened to music through a direct audio cable or through Bluetooth streaming. The training schedule was 40 minutes/session/day, 5 days/week, for either 4 or 8 weeks. The pre-training and post-training tests included: hearing thresholds, Speech, Spatial and Qualities of Hearing Scale (SSQ12) questionnaire, psychoacoustic tests of frequency change detection threshold (FCDT), speech recognition tests (CNC words, AzBio sentences, and QuickSIN), and EEG responses to tones that contained different magnitudes of frequency changes. Results. All participants except one finished the 4- or 8-week training, resulting in a dropout rate of 8.33%. Eleven participants performed all tests except for two who did not participate in EEG tests. Results showed a significant improvement in the FCDTs as well as performance on CNC and QuickSIN after training (p<0.05), but no significant improvement in SSQ scores (p>0.05). Results of the EEG tests showed larger post-training cortical auditory evoked potentials (CAEPs) in 7 of the 9 participants, suggesting a better cortical processing of both stimulus onset and within-stimulus frequency changes. Conclusion. These preliminary data suggest that extensive, focused music listening can improve frequency perception and speech perception in CI users. Further studies that include a larger sample size and control groups are warranted to determine the efficacy of short-term music training in CI users.